Assessment of the Effects of Monetary Policy Shocks from ECOWAS Member Countries to Nigeria - Ohaegbu , Nnaemeka Emmanuel.; Akanegbu , Benedict Ndubuisi. (Journal of Social Science Studies, 2023)
The paper evaluated the effects of monetary policy shocks from ECOWAS Member Countries to Nigeria using a combination of quarterly, annual time-series and panel data spanning from 1995–2021. The Standard Global Vector-Autoregressive (GVAR) Model of analysis was used to draw structural inference for the study using data on: consumer prices, international commodity prices (oil, agricultural raw material and metal ore), exchange rate, interest rate (short and long run), real output, money supply, and export diversification index. The result of the Impulse Response Function (IRF) revealed that shocks resulting from monetary policy transmission from the ECOWAS member Countries to Nigeria has diverse effects on Nigeria and is largely determined by the extent of monetary policy accommodative stance. The shock that may occur is likely to be country-specific because ECOWAS is an economic union that hardly has the foundation to share common economic or monetary risk. Additionally, the extent of trade flow between Nigeria and the rest of ECOWAS, determines the tendency that such shocks affect Nigeria. Finally, whether ECOWAS is a shock source, or a channel of transmission determines how much of an impact shocks from that region will have.